A galvanic exchange process visualized on single silver nanoparticles via dark-field microscopy imaging. Issue 26 (27th June 2018) - Zhou, Jun; Yang, Tong; He, Wei; Pan, Zi Yu; Huang, Cheng Zhi
Abstract : A galvanic exchange (GE) process was visually monitored in real-time using light scattering dark-field microscopy imaging, through which the reaction kinetics of the GE process was visualized and the silver removal rate and gold deposition rate on single nanoparticles were revealed. Abstract : The study of the galvanic exchange (GE) mechanism is beneficial for designing and developing new bimetallic nanocrystal structures with excellent bifunctional catalytic properties. Herein, we have visually demonstrated a GE process by real-time monitoring of the reaction between silver nanoparticles (AgNPs) and Au 3+ at the single nanoparticle level using light scattering dark-field microscopy imaging. The localized surface plasmon resonance (LSPR) scattering spectral shifts of the AgNPs which reveal the Ag removal rate and Au deposition rate on the surface of the AgNPs can be observed. Furthermore, a pixel meta three color channel method has been introduced for analyzing the scattering light color changes of plasmonic particles to reveal the kinetics of the atomic deposition process on a single AgNP during GE, thus making the reaction kinetics of the GE process directly observable. Therefore, this study provides an efficient and promising approach for understanding the GE mechanism and exploiting its reaction kinetics.